Serological trail of Brucella infection in an urban slum population in Brazil (2012)
ABSTRACT: Introduction: Brucellosis is a re-emerging zoonosis with new cases reported each year in many Latin American countries, but it is mostly under-recognized. This study presents a serological investigation of infection with Brucella abortus and Brucella canis in a poor urban community in the city of Salvador, Brazil. Methodology: Human sera (n = 180) were randomly selected from 3,171 samples taken from healthy individuals during 2003-2004 and tested with C-ELISA for B. abortus and I-ELISA for B. canis. Results: Thirteen percent (24/180) of the individuals were positive for B. abortus and 4.6 % (8/174) were positive for B. canis. Among the variables studied only age (older than 45 years) appeared to be a risk factor for the detection of Brucella antibodies.Conclusion: These results indicate the presence of Brucella infection in this settlement and highlight the need to understand the epidemiology of infection under these circumstances to establish the necessary measures for surveillance and control.